2011
DOI: 10.1128/aem.00464-11
|View full text |Cite
|
Sign up to set email alerts
|

Complex Expression of the Cellulolytic Transcriptome of Saccharophagus degradans

Abstract: Saccharophagus degradans is an aerobic marine bacterium that can degrade cellulose by the induced expression of an unusual cellulolytic system composed of multiple endoglucanases and glucosidases. To understand the regulation of the cellulolytic system, transcript levels for the genes predicted to contribute to the cellulolytic system were monitored by quantitative real-time PCR (qRT-PCR) during the transition to growth on cellulose. Four glucanases of the cellulolytic system exhibited basal expression during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Such general induction may be more efficient than a complex regulatory system recognizing various polysaccharides if we consider the variability of these structures. So far, the regulatory systems that respond to the presence of cellulose degradation products such as cellobiose and other cellodextrins remain unknown in most bacteria 35 . However, some studies showed that certain bacteria express glycosyl hydrolases even during growth on glucose 35 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such general induction may be more efficient than a complex regulatory system recognizing various polysaccharides if we consider the variability of these structures. So far, the regulatory systems that respond to the presence of cellulose degradation products such as cellobiose and other cellodextrins remain unknown in most bacteria 35 . However, some studies showed that certain bacteria express glycosyl hydrolases even during growth on glucose 35 36 .…”
Section: Discussionmentioning
confidence: 99%
“…So far, the regulatory systems that respond to the presence of cellulose degradation products such as cellobiose and other cellodextrins remain unknown in most bacteria 35 . However, some studies showed that certain bacteria express glycosyl hydrolases even during growth on glucose 35 36 . One of these studies showed that glucose induced similar CAZymes as cellulose in Clostridium cellulolyticum and that cellulose was more quickly degraded when glucose was present, hypothesizing that this basal expression may mediate a faster response of the bacteria to cellulose availability 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The excitation-emission matrix (EEM) analysis on the overlying water showed a clear oil-related contour (Ex 270-290 nm, Em 330-360 nm, data not shown), which resembles an oil component (C2) of the crude oil (Zhou et al 2013). Interestingly, Saccharophagus degradans, a cellulose degrader (Zhang and Hutcheson 2011), represented 9% of the bacterial community in the overlying water. One possible explanation for the growth of this bacterium is that oil degraders in sediment produced polysaccharide-related biosurfactants (Desai and Banat 1997), such as rhamnolipids by Pseudomonas.…”
Section: Bacterial Community Structures In Sediments and Overlying Watermentioning
confidence: 98%
“…cDNA was then used as a template for RT‐PCR with the primer pairs listed in Table S1. Guanylate kinase ( spoR ) was used as a reference gene (Zhang & Hutcheson, ).…”
Section: Methodsmentioning
confidence: 99%